Strategi Transformasi dan Pelestarian Burayot: Model Pengembangan Ekonomi Kreatif Berbasis Kearifan Lokal di Kabuyutan Garut - Zahra Nursyafa; Zeni Amalia; Wildan Fauzi; Rival Maulan; M. Dimas Pradipta; Naila Aqila; Aprila Azzahra; Natasya Amanda; Nabila Priani; Wulansari, Wulansari; Itto Turyandi (Journal of Economic and Business Advancement, 2026)
This study aims to analyze strategies for the transformation and preservation of burayot as a model for creative economy development based on local wisdom in Kabuyutan Garut. The study employs a conceptual qualitative approach using a systematic literature review method through a synthesis of literature on the creative economy, cultural digitization, and gastronomic tourism. The results indicate that burayot holds potential as cultural capital that can be developed into a community-based creative economy without compromising its traditional authenticity. The threats of modernization, low artisan regeneration, and weak cultural documentation pose the main challenges to the sustainability of burayot. Relevant strategies include the digitization of cultural knowledge, strengthening the participation of the younger generation, digital promotion innovations, and the development of community-based gastronomic tourism to simultaneously strengthen the sustainability of local culture and the local economy.